Conflict and cooperation in environmental management in peri-urban Accra, Ghana - Gough, K.; Yankson, P. (The Peri-Urban Interface: Approaches to Sustainable Natural and Human Resource Use, 2012)
The chapter draws on fieldwork conducted in five villages within the periurban area of Accra: La Bawaleshie, the closest to the centre of Accra and which has been totally surrounded by urban development; Pantang, which lies beyond the physical limit of the city; and Ashale Botwe, Agbogba and Gbawe, which are located between these in the area experiencing the most rapid landuse change (see Figure 14.1). These villages were first studied during 1995/1996, when focus group discussions were held with the chief and elders, youth groups and women’s groups, and a census survey, questionnaires and indepth interviews were conducted in each village. Our interest in these settlements has been ongoing informally since 1995; but in February 2003 we again conducted formal focus group discussions with the same three groups, enabling us to trace the changes that have taken place.